Status Deficits and War. (1st August 2016) - Renshon, Jonathan
Abstract: Despite widespread agreement that status matters, there is relatively little in the way of focused research on how and when it matters. Relying on the assumption that it "matters" has provided few extant theories of variation in states' concern for status and little understanding of its specific implications for international conflict. I introduce a theory of status dissatisfaction (SD) that clarifies who forms the basis for status comparisons in world politics, when status concerns should be paramount, and how they are linked to international conflict. I demonstrate the viability of conflict as a strategy for status enhancement: both initiation and victory bring substantial status benefits over both five- and ten-year periods. Using a new, network-based measure of international status, I demonstrate that status deficits are significantly associated with an increased probability of war and militarized interstate dispute (MID) initiation. Even internationally, status is local: I use "community detection" algorithms to recover status communities and show that deficits within those communities are particularly salient for states and leaders.